Molybdenum isotopic evidence for oxic marine conditions during the latest Permian extinction - Proemse, Bernadette; Grasby, S.; Wieser, M.; Mayer, B.; Beauchamp, B. (Geological Society of America, 2013)
The latest Permian extinction (LPE), ca. 252 Ma, represents the most severe extinctionevent in Earth’s history. The cause is still debated, but widespread marine anoxicto euxinic (H2S rich) conditions, from deep to shallow water environments, are commonlysuggested. As a proxy for marine oxygen levels, we analyzed d98/95Mo of two LPEsections that represent a gradient in water depth on the northwest margin of Pangea.Results from deep-water slope environments show a large shift in d98/95Mo values from–2.02‰ to +2.23‰ at the extinction horizon, consistent with onset of euxinic conditions. Incontrast, sub-storm wave base shelf environments show little change in the molybdenum isotopic composition (–1.34‰ to +0.05‰), indicating ongoing oxic conditions across the LPE.These results indicate that areas of the continental shelf of northwest Pangea underwent massextinction under oxic conditions throughout the LPE event, and that shallow-water anoxiawas therefore not a global phenomenon.